Poetics of Title in Non-Novel Prose by I. A. Goncharov - G. G. Bagautdinova (Научный диалог, 2021)
The novelty of the work is in the fact that for the first time in I. A. Goncharov’s works study, the peculiarities of the poetics of the title in the works of I. A. Goncharov of small and medium genre epic forms, are examined. The relevance of the article is due to the fact that the study of the title, the identification of its typological models will allow to describe the patterns in the artistic system of I. A. Goncharov. A classification of the titles of the writer’s works written in non-novel genre forms is proposed. The classification is based on the dominant structural and semantic features of the titles of the writer’s non-novel fictional prose. The question of the semantics of titles is raised in the article, the attention is paid to their linguistic features. Some questions of the functional interaction of the title with the main text are considered. It is noted that the analysis of various types of titles in the works of I. A. Goncharov showed the importance of this component in the poetics of the writer. The author of the article comes to the conclusion that the analysis of the title allows not only to consider the position of the “total” author, but also to explore many aspects of the writer's poetics: frame text, subject matter, composition, genre, style, narrative system, language.